Pengaruh Pendekatan Etnopedagogi Terhadap Sikap Inklusif Siswa Kelas III SDN Krapyak Wetan Pada Pembelajaran Pendidikan Pancasila - Maftu Hatuz Zahro; Indah Perdana Sari; An-Nisa Apriani; Ismanto Ismanto (Jurnal Pendidikan Sosial Dan Konseling, 2026)
An inclusive attitude needs to be fostered in elementary school students so that they can appreciate differences and work together. However, there are still students who show a lack of appreciation for differences. The ethnopedagogical approach was chosen because it integrates the values of local wisdom into learning. This study aims to determine the effect of the ethnopedagogical approach on the inclusive attitudes of third-grade students at SDN Krapyak Wetan in Pancasila Education lessons. The study employed a quantitative research design using a quasi-experimental method with a Nonequivalent Control Group Design. This study was conducted at SDN Krapyak Wetan with a sample of 47 students, consisting of 25 students in the experimental class and 22 students in the control class. Data were collected using questionnaires and observation sheets. Data analysis involved tests of normality, homogeneity, and the Independent samples t-test. The results showed that the average inclusive attitude score in the experimental class increased from 46.8 to 52.8. The results of the independent samples t-test on the posttest showed a significance value of p < 0.001, indicating a significant difference between the experimental and control classes. Thus, the ethnopedagogical approach had a significant effect on improving the inclusive attitudes of third-grade students at SDN Krapyak Wetan in Pancasila Education lessons.